2010
DOI: 10.1111/j.1600-0625.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of experimental malignant melanoma models to the pan‐Aurora kinase inhibitor VE‐465

Abstract: Aurora kinases represent promising novel cancer therapy targets. Genomic analyses of human cutaneous melanoma (CMM) models (N = 51, low passage) by classical and/or array CGH revealed frequent gains at chromosome 20q (65%, amplifications in 45%) repeatedly including the Aurora A gene locus. Accordingly, the majority of CMM cell cultures overexpressed Aurora A when compared to proliferating non-malignant cells. Moreover, CMM cells even when arrested in G1/S cell cycle phase contained readily detectable levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
(80 reference statements)
1
18
0
Order By: Relevance
“…Cell death by mitotic catastrophe is evidenced by polyploidization, caspase-2 activation, and detection of dead cells. Previous works with pan-Aurora inhibitors in melanoma cells (5,28) and in other tumor types (10,20) reported similar effects. The progressive disappearance of both Cyclin B1 and CDK1 after Aurora B suppression is consistent with cells that exit mitosis without completion of cytokinesis and with cells that enter a new round of cell division at a higher DNA content.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Cell death by mitotic catastrophe is evidenced by polyploidization, caspase-2 activation, and detection of dead cells. Previous works with pan-Aurora inhibitors in melanoma cells (5,28) and in other tumor types (10,20) reported similar effects. The progressive disappearance of both Cyclin B1 and CDK1 after Aurora B suppression is consistent with cells that exit mitosis without completion of cytokinesis and with cells that enter a new round of cell division at a higher DNA content.…”
Section: Discussionsupporting
confidence: 58%
“…Given their function in the control of the G 2 /M phase, the expression of the chromosomal passenger protein complex proteins is controlled in a cell cycle-dependent manner. However, in-creased expression of some of these components such as Aurora B and Survivin has been observed in a spectrum of cancers, including melanoma (5,6), and predicts early tumor recurrence and poor prognosis (7,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, overexpression of Aurora A in NIH-3T3 cells is known to enhanced colony formation and solid tumor formation, as well as being implicated in the emergence of centrosome abnormalities and aneuploidy in breast cancer (45, 46). Previous studies have reported that overexpression of Aurora kinase B contributes to melanoma progression by causing genomic instability and aneuploidy (15, 47). Other work has implicated Aurora kinase in the escape from vemurafenib therapy, with 2 BRAF inhibitor resistant cell lines showing sensitivity to the Aurora kinase B inhibitor AZD1152 (15).…”
Section: Discussionmentioning
confidence: 99%